EPISTEMOLOGICAL DISCOURSE: ISLAMIZATION AND INTEGRATION PARADIGMS OF ISLAMIC SCIENCE - Taufiqurrahman (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This study discusses the paradigm of islamization and integration of science in discourse of epistemology as a tradition of islamic thought, to initiate a conceptual islamization of science. The method used was literature study with a historical approach to observe heuristic aspects, source criticism, and hypotheses. The Islamization of science can be seen from the methods used in a pluralistic, valid, and comprehensive manner, it is considered to exist if it is connected hierarchically as a multidimensional reality. The linkages of knowledge in Islam is an important aspect in Islamic epistemology, where the seeking for knowledge itself is not only an obligation, it is even a form of worship and is related to the values of al-Quran. The integration of Islamic science is a accommodation and absorption of islamic values in general science, as a reintroduction of scientific disciplines into the framework of Islam and the dissemination of Islamic science.